Proposal of Economic Ecological Zoning for the Hydrographic Unit of the Chucumayo Stream - Huarochiri, Lima - Meléndez de la Cruz, Juan Felipe (2021)
The Hydrographic Unit of the Chucumayo Stream is characterized by mountain reliefs, with a typical hydric regime of semi-arid environments. Soils for clean crops are scarce and are located in alluvial terraces in the lower part of the mentioned sub-basin. While in the mountains the slopes are very steep with soils of colluvial origin and with xerophytic vegetation or scrub. Traditionally, in these spaces, the population has adapted these mountain ecosystems by building agricultural terraces. In some sectors of the upper or head part of the sub-basin pastures and lagoons are located that could be conserved and provide an environmental service (tourism, water recharge or scientific research). On the other hand, the expansion of the urban areas of the town of Matucana towards the lower part of the sub-basin of the Chucumayo stream is one more example of the urbanization process that is taking place in the country. The present work of Economic Ecological Zoning updated to the year 2019 shows the possibilities of land use taking into account sustainability criteria.